Detection of a Hypercoagulable State in Nonvalvular Atrial Fibrillation and the Effect of Anticoagulant Therapy - Mitusch, Rolf; Slemens, Hans J; Garbe, Michael; Wagner, Thomas; Sheikhzadeh, Abdolhamid; Diederich, Karl W (Thrombosis and Haemostasis, 1996)
The purpose of the study was to evaluate alterations of the hemostatic system and the effect of anticoagulant therapy in nonvalvular atrial fibrillation. A set of molecular hematologic markers was measured prospectively in 69 patients with atrial fibrillation and 28 age-matched patients in sinus rhythm. Significantly elevated levels of thrombin-antithrombin III complex (8.5 ± 1.6 vs. 2.5 ± 0.3 αg/1; p <0.001), fibrin monomers (27.1 ± 3.2 vs. 13.4 ± 3.7 nM; p <0.001), D-dimers (788 ± 76 vs. 405 ± 46 αg/l; p <0.005), and tissue-type plasminogen activator (9.6 ± 0.5 vs. 7.2 ± 0.5 αg/l; p <0.05) were observed in patients with atrial fibrillation compared to those in sinus rhythm. In a subgroup of patients in whom anticoagulant therapy with oral coumadin or standard intravenous heparin was established after the initial study, hemostatic activation decreased significantly. In conclusion, molecular hematologic markers indicate a hypercoagulable state in atrial fibrillation which may characterize a group of patients at elevated risk for thromboembolic disease.